Is midazolam effective as an antioxidant in preventing reperfusion injury in rat kidney? - (:unkn) unknown (My University, 2002)
This experimental study was designed to investigate whether midazolam has antioxidant effects in reperfused rat kidneys following ischemia. Twenty Wistar Albino rats were incuded in the study. Rats were anesthesized with the mixture of ketamine 90 mg/kg and xylazine 10 mg/kg administered intraperitoneally. Following anesthesia, the rats were divided into two groups. The first group was considered as the control group, whereas the second group received additional midazolam 3.5 mg/kg intraperitoneally. The left kidney was approached via a transabdominal incision and the left renal artery was dissected. Left renal ischemia was created by clamping the left renal artery for 45 minutes. Following the ischemia period, the kidney was reperfused for one hour. Both kidneys were then removed. Half of the left kidneys were immediately immersed in liquid nitrogen for transportation and then frozen at -70 C until measurements of tissue malondialdehyde (MDA) and glutathione (GSH) levels. The remaining halves of the left kidneys and right kidneys were fixed in 10% formalin. The changes which developed during the ischemia-reperfusion period in the left kidney were investigated by histopathological examination and compared with those of the normal contralateral kidney. When compared with the control group, tissue MDA and GSH levels were similar in the midazolam group (p > 0.05). Tubular damage with tubulitis and focal interstitial inflammatory infiltration were observed in histopathological examinations of reperfused left kidneys of the control group. There was PMNL infiltration only in perirenal fat tissue of the midazolam group. Right kidneys were histopathologically normal in both groups. We concluded that within this dosage midazolam does not have any antioxidant effect in reperfused rat kidneys following ischemia.
Keywords: Antioxidants; Glutathione; Lipid peroxidation; Malondialdehyde; Midazolam; Oxygen free radicals; Rat; Renal reperfusion injury